2009
DOI: 10.1227/01.neu.0000330402.20883.1b
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Predictors and Spectrum of Treatment Eligibility With Prospective Protocolized Management of Intracerebral Hemorrhage

Abstract: Previous estimates of poorer outcome in patients with ICH might not apply to contemporary management protocols, especially in patients with a smaller ICH volume. Outcome ranges in various risk categories and modeling of treatment eligibility will help project more realistic prognostication and assist with the design of future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…In logistic regression analysis, after adjusting for potential confounders, we also found that GCS score was independently associated with severity on admission and in‐hospital mortality after PICH, whereby the lower GCS score on admission, the worse severity on admission and greater in‐hospital mortality. These findings correspond with results from many previous studies in which the initial consciousness level evaluated by GCS score was the most important and consistent predictor of ICH outcome and mortality .…”
Section: Discussionsupporting
confidence: 91%
“…In logistic regression analysis, after adjusting for potential confounders, we also found that GCS score was independently associated with severity on admission and in‐hospital mortality after PICH, whereby the lower GCS score on admission, the worse severity on admission and greater in‐hospital mortality. These findings correspond with results from many previous studies in which the initial consciousness level evaluated by GCS score was the most important and consistent predictor of ICH outcome and mortality .…”
Section: Discussionsupporting
confidence: 91%
“…Intraventricular hemorrhage (IVH) is frequently associated with intracerebral hemorrhage 1 , and the volume of associated IVH a significant and independent predictor of mortality and disability in this disease 18 . An external ventricular drain (EVD) is commonly used to control intracranial pressure, and to divert cerebrospinal fluid in the setting of hydrocephalus, but also to help clear ventricular blood 1112 .…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, with regard to brain edema and factors affecting acute functional outcome, the collagenase model is known to cause far more lasting and severe blood-brain barrier rupture and neurological deficits than autologous blood injection (MacLellan et al, 2008). Neither model mimics clinical conditions perfectly, but both may be necessary since human ICH also presents in a wide spectrum of severity ( Jaffe et al, 2009). Nonetheless, the study of short-term free-radical-mediated pathophysiological mechanisms may yet yield significant results in future studies using the autologous blood infusion model, since melatonin's effects may simply be inadequate to overcome the severity of acute-phase collagenase injury.…”
mentioning
confidence: 99%